Finely tuning electrolytes and photoanodes in aqueous solar cells by experimental design. (15th March 2018) - Galliano, Simone; Bella, Federico; Piana, Giulia; Giacona, Giulia; Viscardi, Guido; Gerbaldi, Claudio; Grätzel, Michael; Barolo, Claudia
Graphical abstract: Highlights: The importance of studying a photoelectrochemical cell through a multivariate approach. First demonstration of chemometrics for aqueous solar cells. Investigating how many experimental factors affect solar cell performance. Identifying a benchmark for future studies in the aqueous photovoltaic field. Abstract: If opportunely developed and optimized, aqueous dye-sensitized solar cells can be considered a truly low impact photovoltaic device, with no toxic components. Here we report the use of design of experiments as a useful chemometric technique for the concurrent investigation of a series of experimental factors that directly influence the proper operation of these photoelectrochemical cells. Results obtained enlighten that a solid mathematical-statistical approach is fundamental to support the researchers and effectively drive the experiments towards the achievements of optimal operating conditions of any new energy device, thus bypassing the energy/time consuming steps of traditional monovariate one-factor-at-a-time method.